The women’s role in urban agriculture development. The case of «Ecological agriculture network online vegetable gardens» - Solari Pérez, Karla (2019)
This article analyze the rol of women in the promotion and development of urban agriculture in two districts of South Lima: San Juan de Miraflores and Villa Maria del Triunfo. These experiences are framed in the social responsibility project: «Network of organic farmers, online vegetable gardens» of the Red de Energía del Perú company, and will be analyzed transversally by the sex / gender system.